THE SIGNIFICANCE OF PERINATAL RISK FACTORS IN THE PREVENTION OF MULTIPLE ORGAN FAILURE SYNDROME IN NEWBORNS - Марина Афанасьевна Соколовская (The Publishing House Medicine and Enlightenment, 2022)
The article presents the most significant antenatal, intrapartum, and postnatal risk factors and their impact on the development of multiple organ failure syndrome in newborns. The importance of assessing the risk of adverse outcome (mortality) according to the average harmonic value is demonstrated. The correlation between the number of organs involved in the syndrome and the lethal outcome in newborns is shown. The association of late transfer to artificial lung ventilation of newborns in the development of acute respiratory failure with the adverse outcome of multiple organ failure syndrome has been revealed. Purpose of the study - to improve the accuracy of multiple organ failure prognosis based on the study of perinatal risk factors in newborns. Materials and methods. An observational, cross-sectional, retrospective analysis of 267 case histories of premature newborns treated in the neonatal intensive care department of the Novokuznetsk Malakhovsky Children's Hospital was performed. Results. The studies have shown that pregnancy complications such as severe fetoplacental insufficiency, threatened termination of pregnancy, intrauterine fetal retardation, severe gestosis, polyhydramnios, and birth complications such as acute fetal hypoxia, cord entanglement, weak labor activity, clinical mismatch between the fetus and the mother's pelvis increase the risk of multiorgan failure in the newborn. In addition, the proposed index of combined pregnancy and delivery pathology is informative and makes it possible to predict the development of multiple organ failure syndrome in newborns, correlating well with the number of organs involved in multiple organ failure syndrome. Analyzing postnatal risk factors for the development of multiple organ failure syndrome, it was found that delayed start of respiratory therapy in acute respiratory failure is a major risk factor for neonatal death, regardless of the primary lesion, increasing the number of organs involved in multiple organ failure.